2019
DOI: 10.1016/j.jhin.2018.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the cobas Liat influenza point-of-care test into an emergency department during a high-incidence season: a retrospective evaluation following real-world implementation

Abstract: Influenza was detected in 308 of 1027 (30%) samples tested; influenza A in 157 (15.3%), influenza B in 149 (14.5%) and RSV in 28 (2.7%). When compared against Fast Track Diagnostics Respiratory Pathogens 21 multiplex polymerase chain reaction and Cepheid Xpert Xpress Flu/RSV assay, Liat performance for the detection of influenza A or B was: sensitivity 85% [95% confidence interval (CI) 76e92)], specificity 98% (95% CI 97e99), negative predictive value 94% (95% CI 92e96) and positive predictive value 95% (95% C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 8 publications
1
20
0
Order By: Relevance
“…Two studies compared assays from the cobas Liat system performed in the emergency department to Cepheid“s GeneXpert Xpert Flu assays (rapid central testing) during the 2017–2018 flu season. [32,33] The sensitivity and specificity of the cobas Liat system ranged from 0.85 to 0.99 and 0.96 to 0.99, respectively. The study that reported the lower sensitivity might have been subject to bias because only negative results were systematically centrally controlled, thus increasing the likelihood of false positives.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies compared assays from the cobas Liat system performed in the emergency department to Cepheid“s GeneXpert Xpert Flu assays (rapid central testing) during the 2017–2018 flu season. [32,33] The sensitivity and specificity of the cobas Liat system ranged from 0.85 to 0.99 and 0.96 to 0.99, respectively. The study that reported the lower sensitivity might have been subject to bias because only negative results were systematically centrally controlled, thus increasing the likelihood of false positives.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies [ 30 , [32] , [33] , [34] , [35] , [36] , [37] , [38] ] have assessed and compared the reliability of the Roche Cobas Liat against similar competing devices and concur on its fast and easy-to-use aspects. Adults tested in a “real-world” clinical setting [ 37 ] yielded the lowest values of sensitivity (influenza A: 83.0%, influenza B: 84.6%, RSV: 77.8%) in the literature. Other reports in more classical diagnostic settings generally reported high sensitivity (influenza A: 96.2%–100%, influenza B: 94.4%–100%, and RSV: 96.8%–100%).…”
Section: Today’s Commercial Tools Do Not Combat Pandemicsmentioning
confidence: 99%
“…The high sensitivity and specificity for influenza A, influenza B and RSV found in our study was comparable to previous findings, with better diagnostic accuracy than other routinely available point-of-care devices. [14][15][16][17][18][20][21][22][23][24][25][26][27][28][29][30] The diagnostic accuracy of POCTs for influenza has been examined in individual studies and several systematic reviews. [31][32][33] Although the impact of the cobas® Liat® POCT on clinical decision making during visits to the emergency department has been established, [34] the effect on patient-relevant clinical outcomes still has to be determined.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%